Religion and modernization of India : a case study of northern Orissa - Kanjamala, Augustine, 1939- (Studia Instituti Missiologici Societatis Verbi Divini ;, 1981)
Study of the interaction of Christianity, Hinduism, and modernization, based on data gathered during the 70s.